Selected Total Lipid Analysis Methods from Conventional to Advanced Approaches - Anggara, Jaclyn Regina; Kartikawati, Muliasari; Yoewono, Jessica Renata; Pratiwi, Ika Yohanna (Jurnal Teknologi Pangan, 2026)
Lipids are essential components of food, contributing to nutritional quality, physical properties, and sensory characteristics. Therefore, total lipid analysis is crucial in food evaluation. However, the variety of lipid fractions and the intricacy of food matrices necessitate the use of suitable, precise, and effective analytical techniques. A qualitative narrative review of the evolution of total lipid analysis techniques, including traditional, contemporary, and non-destructive procedures, is presented in this article. International open-access research publications from 2016 to 2025 were used to create the literature, which was then compared according to its constraints, performance, efficiency, and guiding principles. Despite their time and consistency restrictions, traditional solvent-based techniques like Goldfisch, Soxhlet, Bligh and Dyer, and Mojonnier are still often employed because of their ease of use. Higher efficiency and selectivity are provided by contemporary techniques like Supercritical Fluid Extraction (SFE), Microwave-Assisted Extraction (MAE), and Pressurized Liquid Extraction (PLE), while Near-Infrared Spectroscopy (NIRS) has become a quick and effective non-destructive substitute. This review emphasises the importance of integrating conventional and modern methods in total lipid analysis according to the analysis objectives and characteristics of the food matrix.